EFQM model's implementation, in ANAM's case - Freitas, Alice Isabel Rocha e (2012)
Total Quality Management is a worldwide well-known method which aim is to enhance management and employees in a continual improvement in all organizational processes, regardless of location, size or sector. The European Foundation for Quality Management (EFQM) Model is found to be a worthy method to promote quality improvements, even being a generic approach. Ideal for a Excellence journey beginning, the Committed to Excellence (C2E)entry level provided by EFQM, gives knowledge and experience of the „9-Box‟ Model and the RADAR tool logic. Achieving this goal represents a overall organizational effort and commitment, with continual intentions to improve. ANAM is a Airport management enterprise that runs the Madeira Island Airports. Its constructing path to excellence started with the ISO recognitions in 2005, and set in 2009 the aim to achieve the C2E certification. This work objective stands on the description of the internal procedures for this goal, through the all phases inherent to it. Since the initial steps until the identification and implementation on the Projects for the improvement areas, ANAM design which actions should embrace, accordingly with the company and industry features.